2014
DOI: 10.1037/a0036825
|View full text |Cite
|
Sign up to set email alerts
|

A geometric and dynamic affordance model of reaches-to-grasp: Men take greater risks than women.

Abstract: eprints@whiterose.ac.uk https://eprints.whiterose.ac.uk/ Reuse Unless indicated otherwise, fulltext items are protected by copyright with all rights reserved. The copyright exception in section 29 of the Copyright, Designs and Patents Act 1988 allows the making of a single copy solely for the purpose of non-commercial research or private study within the limits of fair dealing. The publisher or other rights-holder may allow further reproduction and re-use of this version -refer to the White Rose Research Onlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Affordances are perceptible, task specific, organism-relative properties of objects and events; not “how large is that object?” but “can the object be grasped by me?” or “can the object be stepped over by me?” (Gibson, 1979; Turvey, Shaw, Reed, & Mace, 1981). Affordances have been studied in a variety of contexts, including locomotion (e.g., Adolph, Eppler, & Gibson, 1993; Fajen, 2007; Snapp-Childs & Bingham, 2009; Warren, 1984; Warren & Whang, 1987), prehension (e.g., Bingham & Muchisky, 1993a, 1993b; Mark et al, 1997; Mon-Williams & Bingham, 2011; Bingham, Snapp-Childs, Fath, Pan, & Coats, 2014), bouncing a ball on a racquet (e.g., Schaal, Atkeson, & Sternad, 1996; Siegler, Bazile & Warren, 2013; Sternad, Duarte, Katsumata, & Schaal, 2001), and interception (e.g., Fink, Foo, & Warren, 2009; Oudejans, Michaels, Bakker, & Dolné, 1996). More recent work has investigated the affordances of objects for maximum distance throwing (Bingham, Schmidt, & Rosenblum, 1989; Zhu & Bingham, 2008, 2010; Zhu, Dapena, & Bingham, 2009; Zhu, Mirich, & Bingham, 2014; Zhu, Shockley, Riley, Tolston, & Bingham, 2013).…”
mentioning
confidence: 99%
“…Affordances are perceptible, task specific, organism-relative properties of objects and events; not “how large is that object?” but “can the object be grasped by me?” or “can the object be stepped over by me?” (Gibson, 1979; Turvey, Shaw, Reed, & Mace, 1981). Affordances have been studied in a variety of contexts, including locomotion (e.g., Adolph, Eppler, & Gibson, 1993; Fajen, 2007; Snapp-Childs & Bingham, 2009; Warren, 1984; Warren & Whang, 1987), prehension (e.g., Bingham & Muchisky, 1993a, 1993b; Mark et al, 1997; Mon-Williams & Bingham, 2011; Bingham, Snapp-Childs, Fath, Pan, & Coats, 2014), bouncing a ball on a racquet (e.g., Schaal, Atkeson, & Sternad, 1996; Siegler, Bazile & Warren, 2013; Sternad, Duarte, Katsumata, & Schaal, 2001), and interception (e.g., Fink, Foo, & Warren, 2009; Oudejans, Michaels, Bakker, & Dolné, 1996). More recent work has investigated the affordances of objects for maximum distance throwing (Bingham, Schmidt, & Rosenblum, 1989; Zhu & Bingham, 2008, 2010; Zhu, Dapena, & Bingham, 2009; Zhu, Mirich, & Bingham, 2014; Zhu, Shockley, Riley, Tolston, & Bingham, 2013).…”
mentioning
confidence: 99%
“…In the current study, we found a relatively small ratio between maximum grip aperture (MGA) and final grip aperture (FGA) of 1.1–1.2, compared with the MGA/FGA ratio of 1.4–1.7 in real grasping tasks (e.g., Eloka & Franz, 2011; Voudouris et al, 2013; Westwood, Danckert, Servos, & Goodale, 2002). Previous studies have also reported smaller MGA/FGA ratios for virtual grasping tasks (Chen & Saunders, 2015, 2016; Westwood et al, 2002), and this finding can be explained by an affordance model (Bingham, Snapp-Childs, Fath, Pan, & Coats, 2014; Mon-Williams, Bingham, 2011), which argues that MGA is an implication of “a safety margin for collision avoidance” and would decrease without the risk of collision.…”
Section: Discussionmentioning
confidence: 69%